Find the square root of
$5 - \sqrt {10} - \sqrt {15} + \sqrt 6 $
Answer
Verified
513k+ views
Hint: - Let the square root of the given equation be\[\left( {{\text{1 + }}\sqrt a - \sqrt b } \right)\], and also use the property which is \[{\left( {a + b - c} \right)^2} = {a^2} + {b^2} + {c^2} + 2ab - 2bc - 2ca\]
Given equation
$5 - \sqrt {10} - \sqrt {15} + \sqrt 6 $
Square root of given equation is
\[\sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } \]
There are four terms in the given equation therefore in the square root of this it has three terms.
So, let \[{\text{1 + }}\sqrt a - \sqrt b = \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } ................\left( 1 \right)\]
Squaring both sides
\[{\left( {{\text{1 + }}\sqrt a - \sqrt b } \right)^2} = {\left( {\sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } } \right)^2}\]
Now, as we know that \[{\left( {a + b - c} \right)^2} = {a^2} + {b^2} + {c^2} + 2ab - 2bc - 2ca\]
\[
\Rightarrow 1 + a + b + 2\sqrt a - 2\sqrt {ab} - 2\sqrt b = 5 - \sqrt {10} - \sqrt {15} + \sqrt 6 \\
\Rightarrow 1 + a + b + 2\sqrt a - 2\sqrt {ab} - 2\sqrt b = 5 + \sqrt 6 - \sqrt {15} - \sqrt {10} \\
\]
So, on comparing
\[
1 + a + b = 5{\text{, }}\sqrt a = \dfrac{{\sqrt 6 }}{2},{\text{ }}\sqrt {ab} {\text{ = }}\dfrac{{\sqrt {15} }}{2}{\text{, and }}\sqrt b = \dfrac{{\sqrt {10} }}{2} \\
\sqrt a = \dfrac{{\sqrt 6 }}{2} \Rightarrow a = \dfrac{6}{4} = \dfrac{3}{2} \\
\sqrt b = \dfrac{{\sqrt {10} }}{2} \Rightarrow b = \dfrac{{10}}{4} = \dfrac{5}{2} \\
\]
From equation (1)
\[
{\text{1 + }}\sqrt a - \sqrt b = \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } \\
\Rightarrow \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } = 1 + \sqrt {\dfrac{3}{2}} - \sqrt {\dfrac{5}{2}} \\
\]
As we know perfect square root always gives us \[ \pm \]condition
\[ \Rightarrow \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } = \pm \left( {1 + \sqrt {\dfrac{3}{2}} - \sqrt {\dfrac{5}{2}} } \right)\]
So, this is the required square root.
Note: -In such types of questions always assume the required square root as above then take square on both sides and compare its terms and calculate the values of $a$ and $b$ then from the equation which we assumed substitute the values of $a$ and $b$ we will get the required square root.
Given equation
$5 - \sqrt {10} - \sqrt {15} + \sqrt 6 $
Square root of given equation is
\[\sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } \]
There are four terms in the given equation therefore in the square root of this it has three terms.
So, let \[{\text{1 + }}\sqrt a - \sqrt b = \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } ................\left( 1 \right)\]
Squaring both sides
\[{\left( {{\text{1 + }}\sqrt a - \sqrt b } \right)^2} = {\left( {\sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } } \right)^2}\]
Now, as we know that \[{\left( {a + b - c} \right)^2} = {a^2} + {b^2} + {c^2} + 2ab - 2bc - 2ca\]
\[
\Rightarrow 1 + a + b + 2\sqrt a - 2\sqrt {ab} - 2\sqrt b = 5 - \sqrt {10} - \sqrt {15} + \sqrt 6 \\
\Rightarrow 1 + a + b + 2\sqrt a - 2\sqrt {ab} - 2\sqrt b = 5 + \sqrt 6 - \sqrt {15} - \sqrt {10} \\
\]
So, on comparing
\[
1 + a + b = 5{\text{, }}\sqrt a = \dfrac{{\sqrt 6 }}{2},{\text{ }}\sqrt {ab} {\text{ = }}\dfrac{{\sqrt {15} }}{2}{\text{, and }}\sqrt b = \dfrac{{\sqrt {10} }}{2} \\
\sqrt a = \dfrac{{\sqrt 6 }}{2} \Rightarrow a = \dfrac{6}{4} = \dfrac{3}{2} \\
\sqrt b = \dfrac{{\sqrt {10} }}{2} \Rightarrow b = \dfrac{{10}}{4} = \dfrac{5}{2} \\
\]
From equation (1)
\[
{\text{1 + }}\sqrt a - \sqrt b = \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } \\
\Rightarrow \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } = 1 + \sqrt {\dfrac{3}{2}} - \sqrt {\dfrac{5}{2}} \\
\]
As we know perfect square root always gives us \[ \pm \]condition
\[ \Rightarrow \sqrt {5 - \sqrt {10} - \sqrt {15} + \sqrt 6 } = \pm \left( {1 + \sqrt {\dfrac{3}{2}} - \sqrt {\dfrac{5}{2}} } \right)\]
So, this is the required square root.
Note: -In such types of questions always assume the required square root as above then take square on both sides and compare its terms and calculate the values of $a$ and $b$ then from the equation which we assumed substitute the values of $a$ and $b$ we will get the required square root.
Recently Updated Pages
Master Class 9 General Knowledge: Engaging Questions & Answers for Success
Master Class 9 English: Engaging Questions & Answers for Success
Master Class 9 Science: Engaging Questions & Answers for Success
Master Class 9 Social Science: Engaging Questions & Answers for Success
Master Class 9 Maths: Engaging Questions & Answers for Success
Class 9 Question and Answer - Your Ultimate Solutions Guide
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Difference Between Plant Cell and Animal Cell
What is pollution? How many types of pollution? Define it
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.